2017
DOI: 10.1002/2016wr020317
|View full text |Cite
|
Sign up to set email alerts
|

A two‐dimensional analytical model of vapor intrusion involving vertical heterogeneity

Abstract: In this work, we present an analytical chlorinated vapor intrusion (CVI) model that can estimate source‐to‐indoor air concentration attenuation by simulating two‐dimensional (2‐D) vapor concentration profile in vertically heterogeneous soils overlying a homogenous vapor source. The analytical solution describing the 2‐D soil gas transport was obtained by applying a modified Schwarz‐Christoffel mapping method. A partial field validation showed that the developed model provides results (especially in terms of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This can result in significantly different predictions of subfoundation soil gas concentration profiles than those with a more realistic continuous variation of moisture content. This concern is further confirmed by a newly published study (Yao et al, 2017), which reported that the predictions of USEPA spreadsheet are higher than the full three-dimensional (3-D) simulations by one to two orders of magnitude in scenarios involving groundwater sources. Although the above studies provided some interesting insights into the influence of soil properties such as moisture content and permeability in VI, there has been no comprehensive investigation of the role of soil texture in the soil gas concentration attenuation processes in scenarios involving groundwater sources.…”
mentioning
confidence: 60%
“…This can result in significantly different predictions of subfoundation soil gas concentration profiles than those with a more realistic continuous variation of moisture content. This concern is further confirmed by a newly published study (Yao et al, 2017), which reported that the predictions of USEPA spreadsheet are higher than the full three-dimensional (3-D) simulations by one to two orders of magnitude in scenarios involving groundwater sources. Although the above studies provided some interesting insights into the influence of soil properties such as moisture content and permeability in VI, there has been no comprehensive investigation of the role of soil texture in the soil gas concentration attenuation processes in scenarios involving groundwater sources.…”
mentioning
confidence: 60%
“…Due to such complexity, a full 3‐D finite element model is used to study the influences of such a preferential pathway on both of these measures. The 3‐D numerical model applied here was developed with COMSOL Multiphysics and has been presented in previous publications (Bozkurt et al, 2009; Pennell et al, 2009; Yao et al, 2011, 2012, 2013a, 2013b, 2013c, 2015, 2017a, 2017b). The numerical model includes two modules, Darcy's law and chemical transport in porous media.…”
Section: Methodsmentioning
confidence: 99%
“…The EPA-JEM, a modified version of the Johnson-Ettinger model developed by USEPA, treats the capillary zone and unsaturated vadose zone soil as two separate, but uniform, layers (USEPA 2017b). The resulting model predicts attenuation factors that are up to two orders of magnitude higher (i.e., more conservative) than those predicted by more robust, three-dimensional numerical simulations and a corresponding two-dimensional analytical model (CVI2D) (Yao et al 2017a). The latter model employs a continuous soil moisture content profile calculated using the van Genuchten equation (van Genuchten 1980), and this same approach is now routinely used in most three dimensional VI computational models.…”
Section: The Use Of a VI Screening Modelmentioning
confidence: 96%